Kornilov from the Kornilov’s family (according to documents of Historical archives of Omsk region) - L. I. Ogorodnikovа; A. M. Losunov (Омский научный вестник: Серия "Общество. История. Современность")
The article is a historical-genealogical study devoted to one of the main leaders of the White movement L. G. Kornilov. On the basis of the source complex, which is first put into scientific circulation, found by the authors in the funds of the Historical archives of the Omsk region, the family history and the origin of the famous general are revealed. Also, the memorialization of L. G. Kornilov in the Omsk region has been comprehensively reviewed